2010
DOI: 10.1152/ajplung.00170.2009
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of epithelial sodium channel activity by lipopolysaccharide in alveolar type II cells: involvement of purinergic signaling

Abstract: Pseudomonas aeruginosa is a gram-negative bacterium that causes chronic infection in cystic fibrosis patients. We reported recently that P. aeruginosa modulates epithelial Na(+) channel (ENaC) expression in experimental chronic pneumonia models. For this reason, we tested whether LPS from P. aeruginosa alters ENaC expression and activity in alveolar epithelial cells. We found that LPS induces a approximately 60% decrease of ENaC apical current without significant changes in intracellular ENaC or surface protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…The role of PLC in generating calcium release has been described in airway epithelial cells and LPS can stimulate PLC in alveolar epithelial cells [4]. It cannot be excluded that such mechanism occurs in 16HBE14o − cells upon LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of PLC in generating calcium release has been described in airway epithelial cells and LPS can stimulate PLC in alveolar epithelial cells [4]. It cannot be excluded that such mechanism occurs in 16HBE14o − cells upon LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa inhibits sodium absorption via ENaC in alveolar epithelial cells [4]. However, it has been reported that airway epithelial cell lines have a tendency to lose their amiloride-sensitivity in culture and that ENaC activity varies according culture conditions of the 16HBE14o − cells [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flagellin of P. aeruginosa inhibits ENaC expression in airway epithelium, reducing Na ϩ absorption to enhance local mucociliary clearance, a mechanism that is attenuated in CF (Kunzelmann et al, 2006). The action of LPS on ENaC was mediated in part by the protein kinase C and phospholipase C pathways and by purinergic signaling (Boncoeur et al, 2010). In intact distal bronchi of porcine lungs, UTP stimulated Cl Ϫ secretion by a Ca 2ϩ -independent mechanism and inhibited Na ϩ absorption by a Ca 2ϩ -dependent mechanism; both effects are likely to favor increased hydration of the airway surface and may therefore be beneficial in CF .…”
Section: E Cystic Fibrosismentioning
confidence: 99%
“…Similarly, purinergic signaling may contribute to the integrated control of ion/liquid homeostasis within the alveolar space. Nucleotide receptors and adenosine receptors (12,22) have been identified in mouse and rat AT2 cells, and ATP or UTP has been reported to regulate Na ϩ and Cl Ϫ transport in cultured rat AT2 cells (23,24). Whether a role for nucleotide release in response to the mechanical stresses of tidal breathing plays a role in regulating human alveolar liquid homeostasis is as yet unknown.…”
Section: From the Department Of Medicine Cystic Fibrosis/pulmonary Rmentioning
confidence: 99%